Shifting surgical archetypes of ICG fluorescent‐angiography for bowel perfusion assessment in cardiogenic shock under ECMO support. Issue 7 (21st April 2022) - Aleman, Rene; Labkovski, Matthew; Patel, Sinal; Zadneulitca, Nikita; Frieder, Joel S.; Rosenthal, Raul J.; Sheffield, Cedric; Navia, Jose; Brozzi, Nicolas A.
Abstract: Summary: Extracorporeal membrane oxygenation (ECMO) has been adopted to support patients with acute severe cardiac or pulmonary failure that is potentially reversible and unresponsive to conventional management. Mesenteric ischemia (MI) can present as a life‐threatening complication in patients receiving veno‐arterial echocardiogram (ECHO) support. Due to the nature and acuity of these conditions, determining adequate perfusion upon surgical intervention is challenging for the operating surgeon, especially in cardiogenic shock (CS) patients on ECMO support persenting low arterial pulsatility. Indocyanine green fluorescent angiography (ICG‐FA) has proven to be useful for real‐time assessment of vascular perfusion, which may help determine the extent of bowel ischemia in patients receiving ECMO support. The case report here‐in presented, breaks the paradigm of performing non‐cardiac surgical procedures on ECMO support via a pioneering visual aid technique. Learning Objective: ICG‐FA is a promising visual intraoperatory technique providing real‐time feedback for the adequate identification and assessment of target tissue/organs. The high morbidity and mortality rates associated to MI and CS—particularly when concomitantly present—hinders salvage surgical therapy. The use of ECMO provides hemodynamic stability This case report highlights the importance of adequate surgical intervention under extracorporeal life support in the presence of both CS and MI. To the authors' knowledge, this is the first report of application of ICG‐FA to evaluate mesenteric perfusion in a patient receiving ECMO support.